2006
DOI: 10.1177/0022022106286921
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Three Cross-Regional Research Studies on Parenting Styles, Individuation, and Mental Health in Arab Societies

Abstract: This is a general introduction to the series of three articles that follows. The study intended to examine cross-regional differences concerning parenting styles, adolescent-family connectedness, and mental health in eight Arab societies. Three questionnaires were administered to 2,893 Arab adolescents in eight Arab societies: Parental Authority Questionnaire, Multigenerational Interconnectedness Scale, and Psychological State Scale. The results of the analysis are presented in the following reports. The stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
87
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 27 publications
8
87
2
1
Order By: Relevance
“…The finding is consistent with the findings of previous studies that found that the authoritarian parenting style was found to be related with difficulties in social-emotional adjustment during the periods of childhood and adolescence (Baumrind, 1991). This finding is contradictory of a previous study of Arabic speaking parents which found that the authoritarian parenting style was perceived as being positive, and not harmful regarding adjustment among adolescents (Dwairy, 2004;Dwairy & Achoui , 2006), and that the authoritarian parenting style is seen as an expression of the positive attitude of parents towards them, characterized by caring, love, respect, and protection.…”
Section: Discussionsupporting
confidence: 85%
“…The finding is consistent with the findings of previous studies that found that the authoritarian parenting style was found to be related with difficulties in social-emotional adjustment during the periods of childhood and adolescence (Baumrind, 1991). This finding is contradictory of a previous study of Arabic speaking parents which found that the authoritarian parenting style was perceived as being positive, and not harmful regarding adjustment among adolescents (Dwairy, 2004;Dwairy & Achoui , 2006), and that the authoritarian parenting style is seen as an expression of the positive attitude of parents towards them, characterized by caring, love, respect, and protection.…”
Section: Discussionsupporting
confidence: 85%
“…Psicodidáctica, 2015, 20(1), Sin embargo, existe evidencia empírica que sugiere que esta combinación de afecto e imposición no siempre se asocia a los mejores resultados en el bienestar psicológico y social de los hijos. Diferentes estudios llevados a cabo en contextos culturales diferentes al anglosajón (Dwairy y Achoui, 2006;Dwairy y Menshar, 2006), en grupos minoritarios étni-cos (Chao, 2001; e incluso en familias con un nivel socio-económico bajo (Hoff, Laursen, y Tardif, 2002), sugieren que el estilo educativo basado fundamentalmente en la imposición y no en el afecto parental (baja aceptación/implicación y alta severidad/imposición), el estilo autoritario, es un estilo educativo adecuado. Por ejemplo, Baumrind (1972) encontró que los adolescentes afro-americanos de familias autoritarias mostraron las mejores puntuaciones en asertividad e independencia.…”
Section: Introductionunclassified
“…Findings reveal that most of the participants experienced ambivalence: While noting family support and the living and financial convenience, the participants mentioned the inconvenience in handling the generational gap, especially their parents' criticis m and the need to live according to social expectations. As mentioned earlier, the Arab society in Israel in general is tradit ional, reflecting more patriarchal, collectiv ist, and conservative values (Dwairy and Achoui 2006). According to the traditional norms of Arab society, young people are subordinate to the old and according to patriarchal norms, all family members obey the father's authority (Barakat n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, since the 1990s, Israeli Arabs are beco ming exposed to liberal, indiv idualist values, with a tendency toward gender equality, values that are prevalent in overall Israeli society (Dwairy and Achoui 2006). As they express a more Western individual orientation, the age of marriage has been delayed among young Israeli Arabs as in the entire Western world, they are likely to speak two or three languages, have academic education and profes sions, are more mobile and feel less obliged to live at their parents' home (as traditionally expected).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation